Comparative study of toxicity of azo dye Procion Red MX-5B following biosorption and biodegradation treatments with the fungi Aspergillus niger and Aspergillus terreus - Almeida, E. J. R. [UNESP]; Corso, C. R. [UNESP] (Elsevier B.V., 2014)
Azo dyes are an important class of environmental contaminants and are characterized by the presence of one or more azo bonds (-N=N-) in their molecular structure. Effluents containing these compounds resist many types of treatments due to their molecular complexity. Therefore, alternative treatments, such as biosorption and biodegradation, have been widely studied to solve the problems caused by these substances, such as their harmful effects on the environment and organisms. The aim of the present study was to evaluate biosorption and biodegradation of the azo dye Procion Red MX-5B in solutions with the filamentous fungi Aspergillus niger and Aspergillus terreus. Decolorization tests were performed, followed by acute toxicity tests using Lactuca sativa seeds and Anemia sauna larvae. Thirty percent dye removal of the solutions was achieved after 3 h of biosorption. UV-Vis spectroscopy revealed that removal of the dye molecules occurred without major molecular changes. The acute toxicity tests confirmed lack of molecular degradation following biosorption with A. niger, as toxicity to L sativa seed reduced from 5% to 0%. For A. sauna larvae, the solutions were nontoxic before and after treatment. In the biodegradation study with the fungus A. terreus, UV-Vis and FTIR spectroscopy revealed molecular degradation and the formation of secondary metabolites, such as primary and secondary amines. The biodegradation of the dye molecules was evaluated after 24, 240 and 336 h of treatment. The fungal biomass demonstrated considerable affinity for Procion Red MX-5B, achieving approximately 100% decolorization of the solutions by the end of treatment. However, the solutions resulting from this treatment exhibited a significant increase in toxicity, inhibiting the growth of L. sativa seeds by 43% and leading to a 100% mortality rate among the A. sauna larvae. Based on the present findings, biodegradation was effective in the decolorization of the samples, but generated toxic metabolites, while biosorption was effective in both decolorization and reducing the toxicity of the solutions. Published by Elsevier Ltd.
Keywords: Industrial effluent; Azo dyes; Microbiological treatments; Filamentous fungi; Acute toxicity